Stories from Pre-service Teachers - Ardiyarso Kurniawan (Yayasan Bina Darma, 2021)
The teaching practicum period is one of the essential components in teacher education programs. It provides opportunities to expose the real world of teaching and advance their knowledge and skills for pre-service teachers. They would encounter various problems and challenges in implementing the theoretical knowledge they have learned in real classrooms at schools. Hence, this study investigates the challenges encountered by pre-service teachers and how they manage those challenges. There were four pre-service teachers of the English Language Education program as the participants in this study. Those participants underwent their teaching practicum at a National Junior High School, Getasan, Kabupaten Semarang. The data were collected from the participants’ reflective journals. Results indicated four major problems that the participants faced; managing anxiety, managing critical moments, managing activities, and managing teaching tools and techniques. Besides, the participants showed various efforts in managing the problems. Furthermore, some recommendations were offered based on the results of this study.